2021
DOI: 10.1007/s10924-021-02345-6
|View full text |Cite
|
Sign up to set email alerts
|

Design of Polyhydroxyalkanoate (PHA) Microbeads with Tunable Functional Properties and High Biodegradability in Seawater

Abstract: Commercial poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBHV) and poly(3hydroxybutyrate-co-3-hydroxyhexanoate) (PHBHHx) were used to prepare microbeads, with diameter ranging from 50 to 100 µm, by an emulsion-evaporation process. The properties of the beads reveal that the elaboration process enables the formation of spherical particles, that the crystallinity of the former polymer is not altered during the process and that the surface roughness of the particles can be tuned by changing the nature of the lat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…Regarding biodegradability, PHBH has been reported to be degraded by Alteromonadaceae in seawater. 48 Volant et al reported that PHBH microbeads enclosed in a container with seawater and sand degraded by 80% in 250 d. 49 Sashiwa et al found that PHBH powder degraded by 31% in 28 d. 5 The film fabricated in the present study degraded by 50% in 14–40 d in a natural environment, which is comparable to the degradation behaviour observed in previous studies. 5 In contrast, more than 50% of the fibre sheets degraded in 7–10 d and almost completely degraded within ∼2 weeks.…”
Section: Resultssupporting
confidence: 87%
“…Regarding biodegradability, PHBH has been reported to be degraded by Alteromonadaceae in seawater. 48 Volant et al reported that PHBH microbeads enclosed in a container with seawater and sand degraded by 80% in 250 d. 49 Sashiwa et al found that PHBH powder degraded by 31% in 28 d. 5 The film fabricated in the present study degraded by 50% in 14–40 d in a natural environment, which is comparable to the degradation behaviour observed in previous studies. 5 In contrast, more than 50% of the fibre sheets degraded in 7–10 d and almost completely degraded within ∼2 weeks.…”
Section: Resultssupporting
confidence: 87%
“…Alternatively, the use of nonbiodegradable nets that one would equip with captors and systematically retrieve from the marine environment might be just as efficient (Fjelstad, 1988;McElwee et al 2012). Other examples include the plastic particles and water-soluble polymers used in care products (e.g., cosmetics, detergents) (Sahlan et al 2020;Volant et al 2021), or the microfibers used in textiles (Fig. 1).…”
Section: Applications For Which the Use Of Biodegradable Plastics Is ...mentioning
confidence: 99%
“…Bio-sourced and biodegradable polymers such as poly(lactic acid) (PLA), poly(hydroxy-alkanoates) (PHAs), and thermoplastic starch (TPS) offer a route to achieving this goal [ 35 ]. These materials are a class of polymers with properties such as stiffness, ductility, and elasticity which can be tuned to suit different applications [ 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. As such, they have the potential to replace a wide range of conventional polyolefins [ 43 ].…”
Section: Introductionmentioning
confidence: 99%